Peaceful coexistence and cultural-civilizational dialogue between Muslims and others in multi-ethnic societies - Muhammad ‘Ashour Abdullah Kushlaf,; Ahmad Yunus Mohd Noor, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The basic principle in Muslims' relations with others is peace and forgiveness. Nothing changes this peaceful relationship except when non-Muslims attack it, directly or indirectly, on the freedom of preaching, or on a Muslim on any land in the homeland of Muslims. As for the relationship of forgiveness, it is fixed under any circumstances. It is based on: the firm belief that the religion of God Almighty is Islam, and considering everything else besides it as false while demonstrating the distinction in the Islamic personality, and not forcing non-Muslims to embrace the true Islamic religion in any way, with the necessity of offering them an invitation and a message, and enabling them to practice the teachings of their religion, and not to insult what they worship so as not to harm the feelings of Muslims. It is historically and realistically established that Muslims are the most capable of peaceful and positive coexistence with those who oppose them in religion, as long as they are committed to their true Islam. It is also necessary to mention the establishment of civilized and cultural dialogue because it is considered an inevitable requirement imposed by the Islamic religion and required by reality, because of its strong link to peaceful coexistence between Muslims and followers of other religions and beliefs in society, and its near and distant fruits are hoped and give meaning to life Diversity and diversity within the community wall, which is reflected in richness in training and renewal in performance and benefit to the general public without exception. Society is an existential necessity dictated by religion and necessitated by reality. Civilized and cultural dialogue is a religious duty and a human interest.